The Initial Result Of The First Living Donor Lung Transplantation Case In Vietnam - Q Do; Viet T Tran; Manh A Hoang; Truong G Nguyen; Huy L Nguyen; Ba T Ta (Journal of Advanced Therapeutic Science, 2018)
Lung transplantation is an established treatment option for patients of end-stage lung diseases. Leading indications include chronic obstructive pulmonary disease, idiopathic pulmonary fibrosis and bronchiectasis, pulmonary arterial hypertension. Living donor lung transplantation (LDLT) was indicated for patients who experience a decline in physical condition and have limited life expectancy and had the better result than from brain dead. The first case of LDLT in Vietnam is 7 year olds boy with difuse congenital bronchiectasis, chronic respiratory failure and cor pulmonale. The right and left lower lobes from father and relative uncle are implanted in a recipient in place of whole right and left lung. The initial result of this recipient showed that lung function recuperated quickly and had no early complications. After 12 months surgery, the recipient had normal physical exercise capacity, subclinical tests in normal limits and no respiratory symptoms, opportunistic infection.
Keywords: Lung transplantation